2015
DOI: 10.1016/j.bbadis.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the interface of the pathological complex of α-synuclein and TPPP/p25

Abstract: The pathological interaction of intrinsically disordered proteins, such as α-synuclein (SYN) and Tubulin Polymerization Promoting Protein (TPPP/p25), is often associated with neurodegenerative disorders. These hallmark proteins are co-enriched and co-localized in brain inclusions of Parkinson's disease and other synucleinopathies; yet, their successful targeting does not provide adequate effect due to their multiple functions. Here we characterized the interactions of the human recombinant wild type SYN, its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 46 publications
3
54
0
Order By: Relevance
“…The distinct interface of the physiological and pathological complexes is a crucial point in our drug targeting strategy. Our analysis revealed that the 147 KAPIISGVTK 156 segment in the flexible CORE region of TPPP/p25 and the 126 EMPSEEGYQDYEPEA 140 segment of the C-terminus of SYN are involved in the formation of the interface of their pathological complex [36]. Massive intracellular aggregation of the N-and C-terminally-truncated TPPP/p25 and SYN or its fragments was established.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 82%
See 2 more Smart Citations
“…The distinct interface of the physiological and pathological complexes is a crucial point in our drug targeting strategy. Our analysis revealed that the 147 KAPIISGVTK 156 segment in the flexible CORE region of TPPP/p25 and the 126 EMPSEEGYQDYEPEA 140 segment of the C-terminus of SYN are involved in the formation of the interface of their pathological complex [36]. Massive intracellular aggregation of the N-and C-terminally-truncated TPPP/p25 and SYN or its fragments was established.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 82%
“…Recently we have suggested a new strategy for the therapeutic treatment of Parkinson's disease by targeting the interface of the pathological TPPP/p25-SYN complex without influencing the physiological interaction of TPPP/p25 with tubulin/microtubules [35,36]. The distinct interface of the physiological and pathological complexes is a crucial point in our drug targeting strategy.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Co‐enrichment and co‐localization of TPPP /p25 and SYN in CHO cells taken up from the medium and in human brain tissues of MSA , PD and AD (mixed type pathology) . Figure reproduced from . Written permission has been obtained from Elsevier.…”
Section: Tppp/p25: the New Hallmark Of Parkinsonismmentioning
confidence: 99%
“…The interaction of TPPP/p25 with SYN has been extensively characterized in our laboratory by a wide repertoire of methodologies including biochemical, biophysical and bioinformatics methods using wild‐type and mutant human recombinant proteins, as well as living cell models for immunofluorescence microscopic studies coupled with or without bimolecular fluorescence complementation technology .…”
Section: Targeting Syn and Tppp/p25: A New Strategy To Address The Chmentioning
confidence: 99%